Self-Assembled Asymmetric Block Copolymer Membranes: Bridging the Gap from Ultra- to Nanofiltration - Yu, H.; Qiu, X.; Moreno, N.; Ma, Z.; Calo, Victor; Nunes, S.; Peinemann, K. (Wiley-VCH Verlag, 2015)
The self-assembly of block copolymers is an emerging strategy to produce isoporous ultrafiltration membranes. However, thus far, it has not been possible to bridge the gap from ultra- to nanofiltration and decrease the pore size of self-assembled block copolymer membranes to below 5 nm without post-treatment. It is now reported that the self-assembly of blends of two chemically interacting copolymers can lead to highly porous membranes with pore diameters as small as 1.5 nm. The membrane containing an ultraporous, 60 nm thin separation layer can fully reject solutes with molecular weights of 600 g mol-1 in aqueous solutions with a water flux that is more than one order of magnitude higher than the permeance of commercial nanofiltration membranes. Simulations of the membrane formation process by dissipative particle dynamics (DPD) were used to explain the dramatic observed pore size reduction combined with an increase in water flux.